PENGARUH LINGKUNGAN KERJA NON FISIK DAN MOTIVASI EKSTRINSIK TERHADAP PRODUKTIVITAS KARYAWAN PT. BIMA SAKTI BAKTI PERSADA LAMPUNG SELATAN - Zuriana, Zuriana; Wibaselppa, Anggawidia; Suwandi, Suwandi; Muchphie, Tomy Chandra (JURSIMA, 2025)
Bima Sakti Bakti Persada is engaged in the production of pre-cast concrete in the form of girders and barriers. This company has problems related to the work productivity of production employees in the company. This research aims to determine the influence of the non-physical work environment and extrinsic motivation on the work productivity of employees in the production department of PT. Bima Sakti Bakti Persada. This type of research is quantitative with associative methods. Data collection was carried out by distributing questionnaires to all production employees of PT. Bima Sakti Bakti Persada, numbering 50 people. Data analysis method uses multiple linear regression (t test and f test). data processing with SPSS version 21 software. The results of this study found that the non-physical work environment and extrinsic motivation had a simultaneous and partial effect on the work productivity of employees in the production department of PT. Bima Sakti Bakti Persada.